Fecal microbiota of diarrheic calves: Before, during, and after recovering from disease - Emma Jessop; David L. Renaud; Adronie Verbrugghe; Dasiel Obregon; Jenniffer Macnicol; Aoife McMahon; Lynna Li; Lisa Gamsjäger; Diego E. Gomez (Journal of Veterinary Internal Medicine)
Abstract Background It is unknown if gastrointestinal dysbiosis in diarrheic calves causes disease or is a consequence of the disease. Objectives Describe the fecal microbiota of calves before, during, and after recovering from diarrhea. Animals Fifteen female Holstein calves of 0 to 21 days old from a single farm. Seven calves remained healthy throughout the study, and 8 developed diarrhea on Day 14. Methods Longitudinal cohort study. Microbiota composition was characterized by amplifying the V4 region of the 16S rRNA gene. Results Diversity (Shannon index) increased with age in healthy and diarrheic calves from Day 3 to 21, but diarrheic calves had a lower diversity on the day diarrhea was first observed (Day 14). By Day 21, diversity increased in calves that recovered from diarrhea and was not significantly different from that of their healthy counterparts (P > .05). Weighted UniFrac distance showed significant differences in the fecal microbiota between diarrheic and healthy calves at Day 14 of age (PERMANOVA, P < .05), but not before or after diarrhea (PERMANOVA, P > .05). Lactobacillus, Clostridium Sensu Stricto 1, and Collinsella were differentially abundant on Day 10 in calves that developed diarrhea on Day 14 (P < .05). Conclusion and Clinical Importance The fecal microbiota of healthy and diarrheic calves evolved similarly during the first 10 days of age but differed significantly on the day of onset of diarrhea. Enriching Lactobacillus, Clostridium Sensu Stricto 1, and Collinsella before diarrhea onset could have been contributed to the development of diarrhea.